2019
DOI: 10.1111/jocn.15048
|View full text |Cite
|
Sign up to set email alerts
|

Variations in indwelling urinary catheter use in four Australian acute care hospitals

Abstract: Aims and objectives To identify the point prevalence of indwelling urinary catheters (IDCs) in adult inpatients in acute care hospitals, and to describe the indications for IDC insertion based on patient age, gender, specialty and hospital. Background Catheter‐associated urinary tract infections (CAUTIs) are preventable healthcare‐associated infections. IDC duration is the strongest predictor of CAUTI, and little is known about characteristics of patients who receive an IDC. Design Two single‐day point prevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
(77 reference statements)
0
5
0
Order By: Relevance
“…The collected data were organized, tabulated and statistically analyzed using (24) who concluded that all patients with age >65 years old who were admitted in the emergency department during one-month period developed CAUTI…”
Section: Methods Of Data Analysismentioning
confidence: 99%
“…The collected data were organized, tabulated and statistically analyzed using (24) who concluded that all patients with age >65 years old who were admitted in the emergency department during one-month period developed CAUTI…”
Section: Methods Of Data Analysismentioning
confidence: 99%
“…Nurses are the main providers of IDC patient education, however, little is known about nurses' understanding and awareness of the information their patients are accessing or information that may be readily available for patients ( Mackay et al, 2018 ). Recent studies identified the knowledge gap amongst nurses, especially in monitoring the ongoing need of IDC, and their unwillingness to remove the catheter as soon as it is no longer required ( Clinical Excellence Commission, 2013 ;De Jaeger, 2011 ;Giles et al, 2019 ). In addition, previous studies reported variability in nurses' knowledge levels and confidence in the decision-making process, in terms of the indication for an indwelling urinary catheter, inser-…”
Section: Discussionmentioning
confidence: 99%
“…The use of this digital information-sharing platform for patients has been shown to enhance patients' self-efficacy and self-care behaviours ( Campbell, Dunt, Fitzgerald, & Gordon, 2015 ). Another advantage of using this digital platform is the convenience and speed of delivering patient information ( Hebden et al, 2014 ), as most IDC insertions occur in acute inpatient settings ( Giles et al, 2019 ). Patients can repeatedly access this information using an application available to be sent to their smartphone, as an email, or short message service (SMS).…”
Section: Article In Pressmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is variation in the figures reported in the literature, it is estimated that approximately 25% of patients admitted to hospital have a urinary catheter during their inpatient stay [ 2 ]. A UK study performed in 2017 found that 18.6% of hospital inpatients had a urinary catheter at any one time [ 3 ]. Despite the relative ubiquity of catheterisation as an intervention, there are several complications associated with this process, including infection, trauma, malignancy, hypersensitivity, blockage, and fistula formation [ 4 , 5 ].…”
Section: Discussionmentioning
confidence: 99%